Improving understanding of outcomes for the minority ethnic population in Northern Ireland - Foley, Brian; Colohan, Carmel; Drumm, Sinéad; Hughes, John (International Journal of Population Data Science, 2025)
Objectives We use the Census 2021 Comprehensive Microdata (C21CM) to establish and better understand outcomes for minority ethnic groups (MEGs) in Northern Ireland, whose population is increasing according to recent censuses. The large sample size of the C21CM facilitates meaningful research on small population groups such as MEGs. Methods We conduct descriptive analysis to identify outcomes for MEGs (as classified in Census 2021) in areas including health, education and employment. Regression modelling is applied to investigate the likelihood of outcomes of interest (for example, self-reported good health, being in employment) among the different MEGs, controlling for person-, household- and area-level factors. We also highlight our engagement with the Racial Equality Subgroup, a representative body for MEGs in Northern Ireland, with the aim of shaping the research questions and ensuring relevance, as well as identifying opportunities for effective dissemination of the research findings. Results The results provide new insight on outcomes for the minority ethnic population in Northern Ireland, availing of the rich and comprehensive data from Census 2021. The focus is on key areas including: Disability and self-reported health Educational attainment Employment Occupation Housing tenure and accommodation type We highlight incidence and the extent of differences in outcomes between MEGs, exploring the association between these outcomes and a range of demographic, socioeconomic and migration-related factors. Furthermore, with the C21CM providing household-level data, it enables us to present results and provide insight beyond the person level; in terms of households with members from the minority ethnic population, we show, for example, the extent of variation in characteristics of interest. Conclusion The findings are intended to support the development of the new strategic approach for racial equality in Northern Ireland beyond 2025, overseen by The Executive Office government department. In this context, it is important to identify the areas where MEGs have positive outcomes and equally, where they face challenges.